Evaluation of the Diversities in the Inflammatory Responses in Cats With Bacterial and Viral Infections - Songul Erhan; Bengu Bilgic; Ezgi Ergen; Mert Erek; Elif Ergul Ekiz; Mukaddes Ozcan; Mehmet Erman Or; Banu Dokuzeylul; Erdal Matur (Veterinary Medicine and Science)
ABSTRACT Background Understanding the nature of inflammatory responses in cats with bacterial and viral infections is essential for accurately managing the infection. This study aimed to investigate the diversities of inflammatory responses between bacterial and viral infections in cats to figure out their role in the pathophysiology of these infections. Methods Seventy‐five owned cats were included in the study. The evaluations were performed based on three groups: healthy control, bacterial infection group (those with bronchopneumonia and gastrointestinal tract and urinary tract infections) and viral infection group (21 with feline coronavirus [FCoV], 3 with feline leukaemia virus [FeLV] and 1 with feline calicivirus), each containing 25 individuals. Total and differential leukocyte counts, C‐reactive protein (CRP), transforming growth factor beta (TGF‐β), interleukin‐6 (IL‐6), tumour necrosis factor‐alpha (TNF‐α), interleukin‐1 beta (IL‐1β) and interleukin‐10 (IL‐10) concentrations were assessed in the blood samples collected from sick and healthy animals. Results No statistically significant difference was noted in serum TNF‐α, IL‐1β and IL‐10 concentrations of the infected cats (p = 0.996, p = 0.160 and p = 0.930, respectively). Serum TGF‐β concentration in the viral infection group was reduced compared to the healthy control (p = 0.001). In contrast, WBC count and IL‐6 and CRP concentrations were increased in the cats with bronchopneumonia, gastrointestinal tract infections and urinary tract infections compared to the healthy control and viral infection groups (p = 0.001, p = 0.001 and p = 0.001, respectively). Conclusion This study revealed significant differences between bacterial and viral infections regarding the fashion of inflammatory responses in cats, and the relevant data will undoubtedly contribute to the management and control of feline infectious diseases, rendering the development of novel therapeutic strategies.